2022
DOI: 10.26464/epp2022016
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of metamorphic core complex formation: Implications for the destruction of the North China Craton

Abstract: Widespread magmatism, metamorphic core complexes (MCCs), and significant lithospheric thinning occurred during the Mesozoic in the North China Craton (NCC). It has been suggested that the coeval exhumation of MCCs with uniform NW-SE shear senses and magmatism probably result from the decratonization event during the paleo-Pacific Plate retreat. Here we use 2-D finite element thermo-mechanical numerical models to investigate critical parameters controlling the formation of MCCs under far-field extensional stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Through time, with further extension, topographic collapse, and erosion of the paleo-highlands, the model shows the formation of syntectonic sedimentary basins that cause an increase in concentration of strain rate into the high-angle conjugate shear zones. With further necking of the upper crust, the strain is more concentrated on the left limb of the conjugate shear zones, and the weak middle–lower crust slowly advects upward resulting in formation of symmetric domes, consistent with findings of Ma et al 13 (Fig. 8b, e ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Through time, with further extension, topographic collapse, and erosion of the paleo-highlands, the model shows the formation of syntectonic sedimentary basins that cause an increase in concentration of strain rate into the high-angle conjugate shear zones. With further necking of the upper crust, the strain is more concentrated on the left limb of the conjugate shear zones, and the weak middle–lower crust slowly advects upward resulting in formation of symmetric domes, consistent with findings of Ma et al 13 (Fig. 8b, e ).…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, it is unknown how this setting of a thickened crust prior to extension can explain the evolution history of the heavily mylonitized detachment fault surface, which is typically exposed at low angles in the field. While some previous modeling studies showed that MCCs can form without a thickened crust 13 , 28 , in this paper we show that the formation of a MCC is attributed to post-orogenic collapse of a thickened crust by investigating the kinematics, timing, and mechanism responsible for formation of the MCCs found in the Cordillera of NA 41 (e.g., the Ruby 53 and Snake Range 54 MCCs). While in the central-southern section of the Cordillera of NA the Pacific-North America motion generated a trans-tensional setting and lithospheric extension following collision of the EPR with the trench at ~30 Ma 41 , in the northern section of the Cordillera of NA, the lithospheric extension and formation of MCCs coincided with the timing of an active convergent plate boundary zone (subduction) 41 (Fig.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation